Невиправне знівечення обличчя - судово-медичні та юридичні аспекти - Голубович, Леонід Львович; Голубович, А. Л.; Голубович, П. Л.; Зубко, Марія Дмитрівна; Куртєв, А. В.; Golubovich, L. L.; Golubovich, A. L.; Golubovich, P. L.; Zubko, M. D.; Kurtev, A. V. (My University, 2017)
Швидкоплинні зміни в економічному, політичному і суспільному житті диктують потребу змін і у правовій сфері, де працюють не тільки юристи а й судово-медичні експерти, основна робота яких полягає у допомозі судово-слідчим органам у встановленні істини в конкретних справах, коли скоєні злочини проти життя, здоров'я, честі чи гідності людини. В роботі аналізуються труднощі, з якими стикається судово-медичний експерт при визначенні ступеня тяжкості спричинених тілесних ушкоджень за критерієм «невиправне знівечення обличчя» і пропонуються шляхи усунення протиріч. Fleeting changes in economic, political and social life dictate the need for changes in the legal field, where the work is not only lawyers but also forensic medical experts, the main job is to help the judicial and investigative authorities in establishing the truth in specific cases where crimes against life, health, honor and dignity. In this article the difficulties with which forensic medical expert has faced during determining the degree of injuries under the criteria of "indelible disfigurement of face" and suggested ways :o resolve the conflicts are analyzed. Objective. Analyzation of forensic and legal approaches to solve questions and to find ways to resolve conflicts. Conclusion. We are convinced that no specialist whether the forensic medical expert, an investigator or a judge can single-handedly solve the problem of disfigurement of face, therefore consider it appropriate to solve the research question withir. is commission or a comprehensive forensic examination, a fundamental part of which is determined by the person that appointed it list of specialists who have the necessary aesthetic ideas to solve the issue on its merits. Order or decision of the representatives o: ie law enforcement bodies confirm the powers of the Commission within the issues to be addressed and, accordingly, take the possi'r'e claims, by the exit of members of the expert committee for the limits of its competence. Despite the fact that our opinion may not be absolutely perfect, this publication we invite experts of forensic experts ir.c lawyers to fruitful discussions and address the issues raised.
Indelible disfigurement of face - forensic and legal aspects
Keywords: судово-медична експертиза; невиправне знівечення обличчя; ступінь тяжкості тілесних ушкоджень; forensic-medical examination; indelible disfigurement of face; the degree of injuries.